An Evaluation of Asset Pricing Models Based on Chinese Stock Market - Zhao, Yifan
Chinese stock market has been growing at a rapid rate since the establishment, and has become the second worldly largest stock market. This study aims to provide a better understanding of the applicability and explanatory power of the Fama-French three-factor model and the Fama-French five-factor model in Chinese stock market. In order to achieve this objective, these two asset pricing models are examined and compared on the basis of Chinese A-share stocks during the period of 01/2010 to 12/2017. Annual financial data and monthly stock market data of A-share listed companies are used.